ETHNOBOTANICAL SURVEY OF PLANTS USED IN THE MANAGEMENT OF DIABETES MELLITUS IN ABEOKUTA, NIGERIA - Kadiri, M; Ojewumi, A W; Agboola, D A; Adekunle, M F (Journal of Drug Delivery and Therapeutics, 2015)
An ethnobotanical survey of some plants used for management of diabetes in Abeokuta, Ogun State, Nigeria was conducted. A total of 100 questionnaires were administered; (50 herbal practitioners and 50 on patients). Investigations were carried out on the plant parts used, methods of preparation and administration including, dosage and duration of usage. The results showed that fifty (50) plant species belonging to 30 families used in herbal anti-diabetes recipes. The most frequently used plant was Vernonia amygdalina (54%), followed by Azadirachta indica (44%), Ocimum gratissimum (20%), Mormodica charantia (10%) and Citrus aurantifolia (10%). Irrespective of the plant parts (leaves, fruits, stem- barks or roots) or combinations of the plant parts, water and alcohol were the main solvents. The most frequently used plant parts was leaf (62%) and mainly by decoction. Treatment regimens were by chewing or drinking of the aqueous herbal preparations (350-400ml) daily for 6-12 weeks or until symptoms of diabetes disappear. Keywords: Anti-diabetic plants, ethnobotanical survey, herbs, plant parts.